A scoping review of the integration of artificial intelligence in primary and secondary schools from 2020 to 2024: Policy implications for South Africa - Saal, Petronella Elize; Chetty, Krish; Ntshayintshayi, Nothando; Moosa, Tahiya; Masuku, Nondumiso (Journal of education (Durban), 2025)
South Africa's education system struggles with challenges highlighted by low student performance in global assessments. Based on Bloom's (1984) personalised instruction model and the Arksey and O'Malley (2005) methodology, this scoping review explores how artificial intelligence (AI) can enhance educational outcomes in South Africa. This analysis of international applications and their implications for South Africa involved a scoping review of SpringerLink, ScienceDirect, Mendeley, and Taylor & Francis databases to identify primary studies on AI in education from 2020 to 2024. Data from 33 articles were charted and summarised according to the research questions. Key findings highlight the potential of AI to provide personalised learning experiences, enhance inclusivity, and support special needs education. However, infrastructure deficiencies pose significant barriers. Effective AI deployment requires educators to develop technical skills and understand AI ethics to address biases and privacy issues. Implications for policy are discussed.